Evaluation of Digital Governance Implementation in the Public Sector: A Study of the Effectiveness of the Smart Governance Program - Muhammad Fadli Akbar (Asian Digital Governance Problems, 2025)
Purpose: This study aims to evaluate the implementation and effectiveness of the Smart Governance Program in Makassar City, Indonesia, particularly in improving public service effectiveness through transparency, responsiveness, and digital accessibility. Subjects and Methods: The study employed a quantitative descriptive-explanatory design involving 200 respondents consisting of government employees and citizens interacting with digital public services. Data were collected through structured questionnaires and analyzed using descriptive statistics, Pearson correlation, and multiple linear regression analysis with SPSS. Results: The findings revealed that transparency, responsiveness, and digital accessibility positively and significantly influenced public service effectiveness. Transparency emerged as the strongest predictor, indicating that open administrative systems and accessible information substantially improve citizen trust and governance performance. Digital governance also improved efficiency, accountability, and service responsiveness, although challenges related to accessibility disparities and institutional coordination persisted. Conclusions: The study concludes that successful smart governance depends not only on technological infrastructure but also on institutional readiness, organizational coordination, and citizen-centered governance practices that strengthen public trust and administrative effectiveness in urban governance transformation.